Acibenzolar-S-methyl and β-amino butyric acid-induced upregulation of biochemical defense against Colletotrichum capsici infection in chilli (Capsicum annuum). (7th February 2020) - Jayapala, Naveen; Hulikunte Mallikarjunaiah, Navya; Puttaswamy, Hariprasad; Gavirangappa, Hithamani; Siddapura Ramachandrappa, Niranjana
Abstract: Abiotic inducers (AI) are synthetic/natural compound, induces systemic resistance in plants against pathogens. Present study aimed to evaluate the foliar application of AI [Acibenzolar-S-Methyl (ASM), and β-Amino Butyric Acid (BABA)] in managing chilli anthracnose under greenhouse conditions. Foliar applications of ASM-5 μg/ml and BABA-10 mM significantly decreases disease incidence to 13.15% and 14.1% respectively, when compared to respective controls (65% and 65.34%). AI treated seedlings recorded maximum H2 O2 accumulation at 9 h (ASM) and 12 h (BABA) after challenged with pathogen. In AI treated seedlings, activity of defense-related enzymes (Phenylalanine ammonia-lyase, Peroxidase, Polyphenol oxidase, Lipoxygenase, and chitinase) was upregulated after challenge inoculation. Similarly, maximum phenolic (μg gallic acid/g tissue) accumulation of 147 and 71.2 was recorded with ASM and BABA treatment, respectively. The AI induced changes in biochemical parameters are in correlation with reduced disease incidence. Hence, AI can use as alternative, safe and eco-friendly candidate to manage chilli anthracnose.